Metabolism and Excretion of the Once-Daily Human Glucagon-Like Peptide-1 Analog Liraglutide in Healthy Male Subjects and Its In Vitro Degradation by Dipeptidyl Peptidase IV and Neutral Endopeptidase - Malm-Erjefält, Monika; Bjørnsdottir, Inga; Vanggaard, Jan; Helleberg, Hans; Larsen, Uffe; Oosterhuis, Berend; van Lier, Jan Jaap; Zdravkovic, Milan; Olsen, Anette K. (Drug metabolism and disposition, 2010)
Liraglutide is a novel once-daily human glucagon-like peptide (GLP)-1 analog in clinical use for the treatment of type 2 diabetes. To study metabolism and excretion of [3H]liraglutide, a single subcutaneous dose of 0.75 mg/14.2 MBq was given to healthy males. The recovered radioactivity in blood, urine, and feces was measured, and metabolites were profiled. In addition, [3H]liraglutide and [3H]GLP-1(7–37) were incubated in vitro with dipeptidyl peptidase-IV (DPP-IV) and neutral endopeptidase (NEP) to compare the metabolite profiles and characterize the degradation products of liraglutide. The exposure of radioactivity in plasma (area under the concentration-time curve from 2 to 24 h) was represented by liraglutide (≥89%) and two minor metabolites (totaling ≤11%). Similarly to GLP-1, liraglutide was cleaved in vitro by DPP-IV in the Ala8-Glu9 position of the N terminus and degraded by NEP into several metabolites. The chromatographic retention time of DPP-IV-truncated liraglutide correlated well with the primary human plasma metabolite [GLP-1(9–37)], and some of the NEP degradation products eluted very close to both plasma metabolites. Three minor metabolites totaling 6 and 5% of the administered radioactivity were excreted in urine and feces, respectively, but no liraglutide was detected. In conclusion, liraglutide is metabolized in vitro by DPP-IV and NEP in a manner similar to that of native GLP-1, although at a much slower rate. The metabolite profiles suggest that both DPP-IV and NEP are also involved in the in vivo degradation of liraglutide. The lack of intact liraglutide excreted in urine and feces and the low levels of metabolites in plasma indicate that liraglutide is completely degraded within the body.